Pre-Polymer Chain Length: Influence on Permanent Memory Effect of PDLC Devices - Mouquinho, A.; Barros, M. T.; Sotomayor, J. (MDPI, 2024)
This study delved into the correlation between the chain length of PEG polymerizable oligomers and the electro-optical properties exhibited by the resultant PDLC films. A range of di(meth)acrylate oligomers derived from polyethylene glycol with varying molecular weights (Mn = 1000, 2000, 4000, and 6000 g mol−1) was synthesized for incorporation as the polymer matrix in PDLC devices. Comprehensive analyses employing 1H-NMR, 13C-NMR, and MALDI-TOF mass spectroscopy were conducted to validate the structure and purity of the synthesized products. The investigation revealed a significant influence of pre-polymer molecular chain length on the thermal properties of the polymer, including amorphousness and crystallinity, which in turn impact the permanent memory effect. Specifically, it was observed that amorphous PEG polymers serve as an ideal matrix for fostering the permanent memory effect in PDLCs. Among the polymerizable PEG oligomers examined, those with a molecular weight of 1000 g/mol yielded polymer chains existing in an amorphous state, exhibiting a glass transition temperature lower than room temperature (−50 °C). This characteristic imparts flexibility and mobility to the polymer matrix chains, facilitating a 37% permanent memory effect. Conversely, longer polymer chains lead to the formation of crystal aggregates, resulting in semi-crystalline polymer matrices. This reduces the malleability of the polymer chains, thereby nullifying the permanent memory effect in the corresponding PDLC devices.
Keywords: polymer-dispersed liquid crystals; memory devices; permanent memory effect; liquid crystals